Social Media Influencers in Virtual Selling Tools: How Do Consumers Perceive the Influencer's Role in Fashion Hauls on Instagram, and How Do These Perceptions Affect Purchase Intentions? - Luisa Mahn (Marketing Review St.Gallen, 2023)
This study examines the perception of the role of social media influencers (SMIs) in the virtual sales tool of fashion hauls from a consumer perspective and its influence on purchase intention. The results show that the role of SMIs is partly comparable to that of traditional salespeople. The behavioral impact depends on the consumers' relationship with the SMIs.
Keywords: 650